2018
DOI: 10.1159/000488859
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Invasion Increases the Risk of Nodal and Distant Recurrence in Node-Negative Stage I–IIA Non-Small-Cell Lung Cancer

Abstract: Objectives: Despite complete surgical resection, 30–40% of patients with stage I–IIA non-small-cell lung cancer (NSCLC) have recurrences. We aimed to elucidate the effect of lymphovascular invasion (LVI) on the prognosis and patterns of recurrence in patients with pathologically confirmed T1–2N0 NSCLC. Methods: We evaluated 381 patients who underwent complete resection and were diagnosed with pathologic T1–2N0 NSCLC between March 2000 and January 2012. Local recurrence, nodal recurrence, and distant metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…The status of vascular invasion was associated with a greater tendency for lymph node metastases, with the highest ORs (3.88, P < 0.0001) in univariate and multivariate logistic analyses. The same conclusion was reached in the study of Sung et al Analysis of the reason might be that the worse the tumor differentiation is, the stronger the invasiveness would be, which leads to early metastasis. The status of vascular invasion suggests that tumor cells invade and migrate along surrounding tiny blood vessels or lymphatic vessels, which might cause early metastasis and poor prognosis.…”
Section: Discussionsupporting
confidence: 68%
“…The status of vascular invasion was associated with a greater tendency for lymph node metastases, with the highest ORs (3.88, P < 0.0001) in univariate and multivariate logistic analyses. The same conclusion was reached in the study of Sung et al Analysis of the reason might be that the worse the tumor differentiation is, the stronger the invasiveness would be, which leads to early metastasis. The status of vascular invasion suggests that tumor cells invade and migrate along surrounding tiny blood vessels or lymphatic vessels, which might cause early metastasis and poor prognosis.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, we recommended that complete dissection both of the lobar lymph node in TBL and NTBL be performed to improve the local control of patients with NSCLC. This suggestion is also supported by previous studies in patients with early stage NSCLC that have suggested similar risk factors for nodal and distant recurrence such as LVI in stage I [ 32 ] or tumor size, tumor differentiation, pleural invasion and bronchus invasion in stage I-IIA [ 33 ] so that complete lymph node dissection should be considered.…”
Section: Discussionsupporting
confidence: 78%
“…LVI is known to be an important prognostic factor for postoperative recurrence and poor prognosis in patients with other cancers [ 21 22 23 ]. Lymphatic invasion was a negative prognostic factor independent of tumor stage in patients with thoracic esophageal squamous cell carcinoma, and lymphatic invasion was a risk factor for lymph node metastasis in T1 tumors and a high risk factor of recurrence in patients without lymph node involvement [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic invasion was a negative prognostic factor independent of tumor stage in patients with thoracic esophageal squamous cell carcinoma, and lymphatic invasion was a risk factor for lymph node metastasis in T1 tumors and a high risk factor of recurrence in patients without lymph node involvement [ 21 ]. LVI was a negative prognostic factor in patients with stage I or IIA non-small cell lung cancer [ 22 ]. Yuan et al [ 23 ] analyzed the impact of LVI in stage I/II colorectal cancer, and showed that LVI is significantly associated with poor OS and RFS.…”
Section: Discussionmentioning
confidence: 99%